Observing HIV-1 5'UTR dimerization with alternating laser excitation single molecule FRET - Blakemore, Robert. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Molecular Microbiology.; Advisor: James Munro.; Committee: Karl Munger, John Coffin, and Katya Heldwein.; Keyword: Molecular biology.; Mature infectious HIV-1 virions contain two copies of a dimerized single stranded RNA genome. Specific packaging of viral RNA is achieved in part by interactions between a dimer structure in the genomes' 5'UTR (untranslated region) and the nucleocapsid (NC) domain of the viral polyprotein Gag. Structural characterization of the interaction between NC and the dimerized 5'UTR would provide insight into the mechanism of specific packaging but the 5'UTR's large size and conformational flexibility make it a challenging target for conventional structural techniques. Studies of in-vitro transcribed segments of the 5'UTR indicate that dimerization initiates via formation of a "kissing-dimer" characterized by intermolecular base-pairing of a six-nucleotide dimer-initiation sequence (DIS). The kissing-dimer may then isomerize into an "extended-dimer" characterized by more extensive intermolecular base-pairing. Subtype specific differences in DIS are associated with differences in in-vitro dimerization behavior which are hypothesized to reflect differences in the tendency to isomerize into extended dimer. This may in turn reflect strain-specific differences in the mechanism of specific packaging, or the architecture of the genome in the mature virion. Here I report on the development and use of an alternating-laser excitation (ALEX) single-molecule FRET based assay to probe the conformation of 5'UTR sequences from HIV-1 subtypes A (strain MAL) and B (strain NL4-3). I found that the unliganded NL4-3 leader predominately forms a stable kissing-dimer in the absence of NC and is converted to an extended dimer by addition of NC or incubation at higher temperature. In contrast the MAL 5' leader mostly formed an unstable dimer that dissociated under conditions suitable for single-molecule FRET observation and effect of higher temperature incubation were modest. The subtype A observations are consistent with formation of an unstable kissing dimer with a small proportion of extended dimer. These results suggest that formation of a kissing dimer interface is sufficient for facilitation of specific packaging and the possibility that there are strain-specific differences in 5'UTR structure in the mature virion. I also investigated whether a monomeric 5'UTR could fold into conformations associated with promoting or inhibiting dimer formation. Full length HIV-1 pre-RNAs have three fates (a) dimerization and packaging into virions (b) translation into Gag and Gag-Pol or (c) splicing into a subgenomic mRNA for translation into other viral proteins. A prior riboswitch-based model for regulation of genome fate has been supplanted by growing consensus around a model wherein genome fate is regulated by variability in transcriptional start usage and its effect on RNA structure. I utilized a smFRET approach to assess the conformation of NL4-3 5'UTR monomers and observed conformations consistent with the transcriptional start site model, in contrast to prior results.